Inovasi dan Kreasi Konten Digital dalam Meningkatkan Efektivitas Dakwah dan Konseling - Nisrina Dzahabiyah Maia; M. Andy Hakim Chandra; Marwah Akilah Salma; Siti Afifatul Ummah (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
Digital transformation has revolutionized Islamic da'wah and counseling services, providing opportunities to reach a wider audience, especially millennials and Gen Z. This study aims to examine digital content innovation and creation that can improve the effectiveness of da'wah and counseling. The method used is a literature review with content-based data analysis, which identifies themes, patterns, and meanings from journals, books, and related digital documents. The results show that digital audiences tend to prefer content that is concise, visual, and easily accessible. Therefore, an effective content development model must encompass research, scripting, production, evaluation, and the selection of an appropriate distribution platform. In digital counseling services, aspects of ethics, privacy, and data security are crucial to maintain user trust. Furthermore, the integration of da'wah messages with counseling in a single platform is considered effective in simultaneously meeting the spiritual and psychological needs of the community. Challenges faced include information overload, misinformation, low digital literacy, and the risk of data breaches. In conclusion, the success of digital da'wah and counseling depends on understanding the audience and implementing a creative and ethical model, to provide a sustainable positive impact.